Role of epigenetics in aetiology and therapies for Type 1 Diabetes Mellitus: A narrative review - Yahaya O Tajudeen; Ufuoma B Shemishere (Journal of Health and Social Sciences)
Introduction: Abundant literature has established the negative impact of traditional media on body image and disordered eating behaviors among young women. In the past few years, social media use has soared especially among youth, yet the influence of social media in relation to disordered eating has not been fully explored. The aim of this study was to assess the relationship between social media use and disordered eating outcomes among young Arab women. Methods: A cross-sectional study was carried out using a probability sample of 1,418 undergraduate female students living in Qatar, a rapidly developing nation in the Middle East. Popular social media platforms were assessed including Instagram, Snapchat, Facebook, and Twitter. Other covariates assessed included body image, body mass index, and socioeconomic status. To assess the multivariate association between social media (main predictor or exposure variable), and disordered eating as measured by three levels of the 26-item Eating Attitudes Test (EAT-26) (dependent variable), stepwise backward ordinal regression models were fit to the data. Data analysis was performed using Stata 14 software. Results: Findings confirmed that intensive use of social media, particularly Instagram, was positively associated with increased disordered eating behaviors among young women. Social media use intensity showed a significant association with increased disordered eating [(OR 1.207, SE (0.075), P < 0.01, 95% Confidential Interval [CI] 1.068 to 1.363)]. Among the four social media platforms measured, Instagram use had a significant association with disordered eating [OR 1.387, SE (0.186), P < 0.05, 95% CI 1.107 to 1.804)]. Discussion and Conclusions: This study highlights the significant role of social media on the behavior of young women, and supports the sociocultural theory linking media to disordered eating. Such an understanding of social media’s role is instrumental for the promotion and prevention of disordered eating among young women.